Development of a pressure sensor system for unobtrusive monitoring of abdominal muscle activities. (3rd April 2018) - Lee, Joonnyong; Park, Jonghyun; Lee, Kyu Jin; Cho, Minkyung; Kim, Keewon; Kim, Hee Chan; Chung, Sun Gun
Abstract: Surface electromyogram (sEMG) is often used by to objectively measure muscular activity during rehabilitation exercises. sEMG is accurate, but it is unsuitable for uses outside the clinic, and patients can benefit from an unobtrusive device which can be readily used to ubiquitously measure abdominal muscle activation. In this study, we present a pressure sensor system which can be latched onto a belt to measure abdominal muscle activation. sEMG and pressure sensor output were measured in 15 healthy young males during isometric trunk flexion exercise (public trials registration number, KCT0002351), and the results were highly correlated (median R  > 0.939). As initial contact force can change the pressure sensor sensitivity, the experiment was performed at two different levels of belt tightness, but the correlations did not significantly improve after tightening the belt, suggesting that the system can be used to ubiquitously and unobtrusively monitor abdominal muscle activity with minimal discomfort.